Cannabinoid receptor 2 evolutionary gene loss makes parrots more susceptible to neuroinflammation - Divín, Daniel; Goméz Samblas, Mercedes; Kuttiyarthu Veetil, Nithya; Voukali, Eleni; Świderská, Zuzana; Krajzingrová, Tereza; Těšický, Martin; Beneš, Vladimír; Elleder, Daniel; Bartoš, Oldřich; Vinkler, Michal (Proceedings. Biological sciences, 2022)
In vertebrates, cannabinoids modulate neuroimmune interactions through two cannabinoid receptors (CNRs) conservatively expressed in the brain (CNR1, syn. CB1) and in the periphery (CNR2, syn. CB2). Our comparative genomic analysis indicates several evolutionary losses in the CNR2 gene that is involved in immune regulation. Notably, we show that the CNR2 gene pseudogenized in all parrots (Psittaciformes). This CNR2 gene loss occurred because of chromosomal rearrangements. Our positive selection analysis suggests the absence of any specific molecular adaptations in parrot CNR1 that would compensate for the CNR2 loss in the modulation of the neuroimmune interactions. Using transcriptomic data from the brains of birds with experimentally induced sterile inflammation we highlight possible functional effects of such a CNR2 gene loss. We compare the expression patterns of CNR and neuroinflammatory markers in CNR2-deficient parrots (represented by the budgerigar, Melopsittacus undulatus and five other parrot species) with CNR2-intact passerines (represented by the zebra finch, Taeniopygia guttata). Unlike in passerines, stimulation with lipopolysaccharide resulted in neuroinflammation in the parrots linked with a significant upregulation of expression in proinflammatory cytokines (including interleukin 1 beta (IL1B) and 6 (IL6)) in the brain. Our results indicate the functional importance of the CNR2 gene loss for increased sensitivity to brain inflammation.
Keywords: gene loss; cannabinoid receptor pseudogenization; avian immunology; cannabinoid receptors; Animals; neural inflammation; neuroimmunology; receptory kanabinoidní; zvířata; Receptors, Cannabinoid; papouškovití; Parrots